2020
DOI: 10.3389/fneur.2020.00428
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Characteristics and Outcomes of Adult Patients in Northwest Ethiopia

Abstract: Stroke is becoming one of the leading causes of adult disability and death in sub-Saharan African countries. The aim of the present study is to provide an up-to-date account of the clinical and demographic characteristics of patients with stroke admitted to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
(28 reference statements)
3
20
1
Order By: Relevance
“…Hemiparesis leftsided 45 (40.5%) and right-sided 40 (36%), was the common chief complaint reported by our study participants on arrival to the hospital which is higher (36-39.7% and 21.9-29.1%, respectively) than the study reported by Temesgen et al 20 and Fikadu et al 21 The other study done in North West Ethiopia reported 81.1% of patients with stroke who sought medical treatment had hemiparesis or hemiplegia. 32 The present study also showed that 94 (84.7%) of patients had at least one comorbid condition/antecedent risk factors, ischemic stroke 74 (83.1%) and hemorrhagic stroke 19 (95.0%), before admission for stroke. Hypertension was the most frequent, ischemic stroke 39 (44.1%) and hemorrhagic stroke 9 (45.0%), antecedent risk factor identified.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Hemiparesis leftsided 45 (40.5%) and right-sided 40 (36%), was the common chief complaint reported by our study participants on arrival to the hospital which is higher (36-39.7% and 21.9-29.1%, respectively) than the study reported by Temesgen et al 20 and Fikadu et al 21 The other study done in North West Ethiopia reported 81.1% of patients with stroke who sought medical treatment had hemiparesis or hemiplegia. 32 The present study also showed that 94 (84.7%) of patients had at least one comorbid condition/antecedent risk factors, ischemic stroke 74 (83.1%) and hemorrhagic stroke 19 (95.0%), before admission for stroke. Hypertension was the most frequent, ischemic stroke 39 (44.1%) and hemorrhagic stroke 9 (45.0%), antecedent risk factor identified.…”
Section: Discussionsupporting
confidence: 70%
“…16,21,28 In this study, according to WHO clinical criteria, ischemic stroke was found the most common type of stroke accounting for 80.1% of the cases, which is much higher than other studies, conducted in different hospitals in Ethiopia where the proportion of Ischemic stroke ranges from 31.5% to 69.4%. 12,19,20,[29][30][31][32] However, this finding was contrary to other studies in the country where hemorrhagic stroke was the most prevalent among stroke patients. 10,28 This could be due to differences in the prevalence of cardiovascular risk, where the previous study reported high hypertension prevalence.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations